The Influence of Online Customer Reviews and Prices on Product Purchasing Decisions Fashion on the Shopee Marketplace in Bekasi - Wulandari, Ayu; Utami, Noviandari Sari; Sarlata, Jufri (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to determine the effect of Online Customer reviews and Price on the decision to purchase Fashion products on the Shopee Marketplace in Bekasi. This study is quantitative research with the type of descriptive research. The data collection method used is a questionnaire. The population in this study is Shopee users who live in Bekasi with the number of unaccounted for. Sampling using Cochran's formula as many as 96 people with purposive sampling type of sampling. Data analysis techniques using multiple linear regression and using SPSS applications 25. Results of this study show that the influence of online customer reviews on purchase decisions by 40.6%, prices affect the purchase decisions by 62.8%. So that online customer reviews and prices influence significantly to the decision to purchase fashion products on the Shopee marketplace in Bekasi. Variable online customer review and price significant effect against simultaneous purchase decisions by 67.5%, of which 32.5% influenced by other variables not studied in this study.